2016
DOI: 10.1136/svn-2016-000020
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure management in acute stroke

Abstract: Blood pressure (BP) is elevated in 75% or more of patients with acute stroke and is associated with poor outcomes. Whether to modulate BP in acute stroke has long been debated. With the loss of normal cerebral autoregulation, theoretical concerns are twofold: high BP can lead to cerebral oedema, haematoma expansion or haemorrhagic transformation; and low BP can lead to increased cerebral infarction or perihaematomal ischaemia. Published evidence from multiple large, high-quality, randomised trials is increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 104 publications
0
38
0
5
Order By: Relevance
“…and Cushing's reflex (a vasopressor response in response to increased intracranial pressure) (4)(5)(6)(7)(8). Whilst this hypertensive response is typically self-limiting (9), it has been associated with poor outcome (10).…”
Section: Introductionmentioning
confidence: 99%
“…and Cushing's reflex (a vasopressor response in response to increased intracranial pressure) (4)(5)(6)(7)(8). Whilst this hypertensive response is typically self-limiting (9), it has been associated with poor outcome (10).…”
Section: Introductionmentioning
confidence: 99%
“…13 The most common stroke type among participants in this study is ischaemic (54%) and this is consistent with several epidemiologic studies. 8,[14][15][16] The findings of the current study indicated that older stroke patients presented with poorer oral hygiene. Old age as a stage in life is associated with declining personal hygiene which has been linked to self-neglect.…”
mentioning
confidence: 49%
“…The relapse frequency depends on the subtype of stroke and is the highest in patients who have suffered from stroke due to embolism of cardiac origin, and in cases of a significant stenosis of the carotid arteries [27]. At the same time, high blood pressure is a high-risk factor for patients in all age groups, which further increases the risk of recurrent stroke [65,66,67].…”
Section: Discussionmentioning
confidence: 99%